2012
DOI: 10.6061/clinics/2012(12)06
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical thrombectomy with solitaire stent retrieval for acute ischemic stroke in a Brazilian population

Abstract: OBJECTIVE:Large vessel occlusion in acute ischemic stroke is associated with low recanalization rates under intravenous thrombolysis. We evaluated the safety and efficacy of the Solitaire AB stent in treating acute ischemic stroke.METHODS:Patients presenting with acute ischemic stroke were prospectively evaluated. The neurological outcomes were assessed using the National Institutes of Health Stroke Scale and the modified Rankin Scale. Time was recorded from the symptom onset to the recanalization and procedur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 36 publications
0
10
0
1
Order By: Relevance
“…Incidence for the end of the event and determine recanalization of TICI classification standard and a large, prospective, multicenter, randomized, controlled study of SWIFT consistent [ 11 ], several studies have shown that stent supports bolt extraction for treatment of acute cerebral infarction caused by artery occlusion, specific and effective rate of blood vessels, can effectively save in ischemia half dark band of tissue cells, improve the clinical outcomes for patients with malignant cerebral infarction [ 12 - 15 ], preoperative diffusion and perfusion imaging, judging ischemia half the size of the dark band, and also carries on intravascular should decide whether the important basis [ 16 , 17 ]. A large meta-analysis showed that intravenous thrombolysis of the great vessels take rate less than 30%, however stents should be used to achieve TICI block blood vessels - 3 level was 93.3%, the rate of over 90 days [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Incidence for the end of the event and determine recanalization of TICI classification standard and a large, prospective, multicenter, randomized, controlled study of SWIFT consistent [ 11 ], several studies have shown that stent supports bolt extraction for treatment of acute cerebral infarction caused by artery occlusion, specific and effective rate of blood vessels, can effectively save in ischemia half dark band of tissue cells, improve the clinical outcomes for patients with malignant cerebral infarction [ 12 - 15 ], preoperative diffusion and perfusion imaging, judging ischemia half the size of the dark band, and also carries on intravascular should decide whether the important basis [ 16 , 17 ]. A large meta-analysis showed that intravenous thrombolysis of the great vessels take rate less than 30%, however stents should be used to achieve TICI block blood vessels - 3 level was 93.3%, the rate of over 90 days [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Stroke patients 80 years or older were allowed to receive the treatment under restricted conditions. 11 One may question whether the low-and middle-income countries are following the right pathway to the future of acute stroke treatment, chasing the boundaries of the therapeutic window using thrombolytic therapy with sophisticated imaging protocols and expensive recanalization tools affordable for few individuals. This was confirmed in a recent publication, where a significant proportion of elderly stroke patients received IV rtPA in a major Brazilian metropolitan area.…”
Section: Outlook Of Stroke Thrombolysis In Chinamentioning
confidence: 99%
“…It is also considered one of the main causes of disabilities [5] resulting not only in persistent neurological deficits, but also in a high physical deconditioning that propagates disability, leading to metabolic abnormalities that significantly increase the risk of myocardial infarction and recurrent stroke [6]. …”
Section: Introductionmentioning
confidence: 99%